A synopsis of the fleas (Insecta: Siphonaptera) parasitizing New World species of Soricidae (Mammalia: Insectivora) - Morrone, Juan J.; Acosta, Roxana (Zootaxa, 2006)
A synopsis of the 57 species and 24 genera of New World fleas parasitizing species of Soricidae is provided, with synonymical lists, and distributional and host data. Species analyzed belong to the families Ceratophyllidae (10 genera), Ctenophthalmidae (10 genera), Hystrichopsyllidae (two genera), and Leptopsyllidae (two genera). Three subspecies are elevated to species: Corrodopsylla lira, C. obtusata, and Nearctopsylla hygini. Soricid hosts include 17 species of Sorex, four species of Cryptotis, two species of Blarina, and one species of Crocidura. The species hosting the highest number of flea species is Blarina brevicauda (19 flea species), followed by Sorex cinereus (16), S. pacificus (9), S. trowbridgii (8), S. fumeus (7), S. palustris (7), and Cryptotis parva (7). Most of the flea species analyzed are polyxenous, and belong mainly to genera associated to small rodents and marginally present on Soricidae. The association with Soricidae seems to be more evident in species of Corrodopsylla, Corypsylla, Ctenophthalmus, Doratopsylla, Hystrichopsylla,and Nearctopsylla. Only Corrodopsylla lira, C. barrerai, Ctenophthalmus cryptotis, C. expansus, C. myodosus, Hystrichopsylla cryptotis, H. guatemalensis, Nearctopsylla georgiana, N. pfitzeri, and N. princei are apparently stenoxenous or monoxenous. Taxa analyzed belong to the Nearctic biotic element and are specially diversified in the Mexican Transition Zone.